Utilization of RNA in situ Hybridization to Understand the Cellular Localization of Powassan Virus RNA at the Tick-Virus-Host Interface - Hermance, Meghan E.; Thangamani, Saravanan (Frontiers in Cellular and Infection Microbiology, 2020)
Skin is the interface between an attached, feeding tick and a host; consequently, it is the first line of defense against invading pathogenic microorganisms that are delivered to a vertebrate host together with tick saliva. Central to the successful transmission of a tick-borne pathogen are complex interactions between the host immune response and early tick-mediated immunomodulation, all of which initially occur at the skin interface. The focus of this work was to demonstrate the use of RNA in situ hybridization (RNA ISH) as a tool for understanding the cellular localization of viral RNA at the feeding site of Powassan virus (POWV)-infected Ixodes scapularis ticks. Intense positive staining for POWV RNA was frequently detected in dermal foci and occasionally detected in hypodermal foci after 24 hours of POWV-infected tick feeding. Additionally, duplex chromogenic RNA ISH staining demonstrated co-localization of POWV RNA with Mus musculus F4/80 RNA, CD11c RNA, vimentin RNA, Krt14 RNA, and CD3ε RNA at the feeding site of POWV-infected ticks. In future studies, RNA ISH can be used to validate transcriptomic analyses conducted at the tick-virus-host cutaneous interface and will provide cellular resolution for specific gene signatures temporally expressed during infected tick feeding. Such a systems biology approach will help create a more refined understanding of the cellular and molecular interactions influencing virus transmission at the cutaneous interface.